Nowcasting: Timely indicators for monitoring risk of poverty in 2014-2016 - Katrin Gasior; Olga Rastrigina (University of Essex, Institute for Social and Economic Research (ISER), 2017)
The at-risk-of-poverty rate (AROP) is one of the three indicators used for monitoring progress towards the Europe 2020 poverty and social exclusion reduction target. Timeliness of this indicator is crucial for monitoring of the social situation and of the effectiveness of tax and benefit policies. However, partly due to the complexity of EU-SILC data collection, estimates of the number of people at risk of poverty are published with a significant delay. This paper extends and updates previous work on estimating ('nowcasting') indicators of poverty risk using the tax-benefit microsimulation model EUROMOD. The model's routines are enhanced with additional adjustments to the EU-SILC based input data in order to capture changes in the employment characteristics of the population since the data were collected. The nowcasting method is applied to twenty-seven EU Member States. Median income and AROP rates are estimated up to 2016. The performance of the method is assessed by comparing the predictions with actual EU-SILC indicators for the years for which the latter are available. If nowcasts are unreliable we explain the main reasons behind the differences between the nowcasted and SILC-based indicators. For countries with stable and reliable results we discuss the main drivers behind the nowcasted trends.
Keywords: C81; H55; I3; 330; Nowcasting; At-risk-of-poverty; European Union; Microsimulation